Molecular mechanisms of Bdp1 in TFIIIB assembly and RNA polymerase III transcription initiation - Jerome Gouge (Nature Portfolio, 2017)
Transcription initiation by RNA polymerase III requires TFIIIB, a complex formed by Brf1/Brf2, TBP and Bdp1. Here, the authors describe the crystal structure of a Brf2-TBP-Bdp1 complex bound to a DNA promoter and characterize the role of Bdp1 in TFIIIB assembly and pre-initiation complex formation.